2021
DOI: 10.3389/fmolb.2021.744363
|View full text |Cite
|
Sign up to set email alerts
|

SNX20AR/MiRNA-301a-3p/SNX20 Axis Associated With Cell Proliferation and Immune Infiltration in Lung Adenocarcinoma

Abstract: Lung cancer is the most common tumor with severe morbidity and high mortality. Increasing evidence has demonstrated that SNX20 plays crucial roles in the progression of human cancer. However, the functions and mechanism of SNX20 in LUAD are still barely known. Here, we employ the TCGA, GEO and CCLE databases to examine the expression of SNX20 in human varies cancer, the results shown that SNX20 is down-regulated in lung Adenocarcinoma, SNX20 level was significantly positive correlated with poor prognosis and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Our previous work showed that SNX20 was down-regulated in NSCLC, overexpression of SNX20 inhibited cell growth and migration abilities of NSCLC cells [ 14 ]. However, no studies have reported the functions of SNX20 in LGG.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work showed that SNX20 was down-regulated in NSCLC, overexpression of SNX20 inhibited cell growth and migration abilities of NSCLC cells [ 14 ]. However, no studies have reported the functions of SNX20 in LGG.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 The pairing between miRNA and target mRNA may not be specific, thereby allowing miRNAs to regulate a wide range of mRNA targets. 43 miRNA is involved in all cell activity regulation, including cell proliferation, 44,45 differentiation, 46 apoptosis, 47 and pyroptosis. 48 lncRNAs are also transcribed by RNA polymerase II and play a key role in gene activation and silencing, alternative splicing, and posttranslational modification in organisms.…”
Section: Ncrnasmentioning
confidence: 99%
“…The pairing between miRNA and target mRNA may not be specific, thereby allowing miRNAs to regulate a wide range of mRNA targets 43 . miRNA is involved in all cell activity regulation, including cell proliferation, 44,45 differentiation, 46 apoptosis, 47 and pyroptosis 48 …”
Section: The Role Of Ncrnas In Diabetes and Vcdmentioning
confidence: 99%
“…Human SASH3 full-length cDNA was synthesized (Shanghai Generay Biotech) and sub-cloned into pCDH-CMV-E2F-eGFP lenti-viral vector. Lenti-viruses were generated according to the manufacturer's protocol as previously documented (23), and indicated cells were infected by viruses twice with 48 h and 72 h viral supernatants containing 4 mg/ml polybrene, and stable cell lines were established by appropriate puromycin selection.…”
Section: Constructs Lenti-viral Preparation and Establishment Of Diff...mentioning
confidence: 99%
“…The qRT-PCR assay was performed as documented (23). The primer sequences are listed as follows: SASH3-F: GTGATTTCCCGAACCATGAACA, SASH3-R:…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%